Selection of enterprise resource planning (ERP) systems - D. Das Neves; D. Fenn; P. Sulcas (South African Journal of Business Management, 2004)
In order to determine the process organisations go through in selecting an Enterprise Resource Planning (ERP) system, a field study was undertaken on eleven cases. Based on the findings a best practice selection process is proposed.A benchmark selection criteria checklist was drawn up as part of this investigation and each of the criteria listed should be considered prior to final selection.Other Issues discussed in this article include the original motivation and justification for ERP purchase, change management, customisation of source code and the roles of the selection committee, consultants and vendors.
Keywords: 650